“Makes you proud to be black eh?”: Reflections on meaningful Indigenous research participation - Kelly, J.; Saggers, Sherry; Taylor, K.; Pearce, G.; Massey, P.; Bull, J.; Odo, T.; Thomas, J.; Billycan, R.; Judd, J.; Reilly, S.; Ahboo, S. (International Society for Equity in Health, 2012)
Introduction: This article outlines the meaningful participation of eight Aboriginal and Torres Strait Islander community members employed as community researchers investigating the impact of pandemic influenza in rural and remote Indigenous communities in Australia. Aboriginal and Torres Strait Islander participation is now a requirement of health research involving Aboriginal and Torres Strait Islander communities. There is a growing literature on the different approaches to such involvement. Fundamental to this literature is an acknowledgement that Indigenous communities are no longer prepared to be research objects for external, mostly non-Indigenous researchers, and demand a role in decisions about what is researched and how it will be researched. In this paper, we describe the protracted process for site identification and recruitment and training of community researchers. We focus on the backgrounds of the Indigenous researchers and their motivations for involvement, and the strengths and challenges posed by Indigenous people researching in their own communities. Throughout the paper our concern is to document how genuine participation and the building of research capacity can occur.Discussion: A key feature of the research was the employment, training and strengthening the capacity of local Aboriginal and Torres Strait Islander community members in the role of community researchers. A series of training workshops were conducted in northern Australia and focussed on qualitative research methods, including data collection, data analysis and writing. The Indigenous researchers collected the community-based data, and worked in partnership with experienced academic researchers in the analysis and compilation of community reports. Parts of those community reports, as well as additional information supplied by the community researchers, forms the basis of this article. As the demand increases for involvement of Indigenous community members as researchers, focus needs to be paid to what constitutes meaningful participation. If active participation in all aspects of the research process is intended, this necessitates close attention to the knowledge and skills required for this to occur at every stage. Building research capacity means not simply equipping local people to undertake research on a particular project, but to have the knowledge and skills to undertake research in other areas. Conclusions: There are considerable benefits for Indigenous people researching in their own communities. Most important for the community researchers on this project was the sense that they were doing important health work, not just conducting research. Given the persistent gaps between Indigenous and non-Indigenous health, this is perhaps one of the most important contributions of this type of research. Whilst research outcomes are undoubtedly important, in many cases the process used is of greater importance.